IMPLEMENTASI PENANAMAN KARAKTER RELIGIUS MELALUI BUDAYA SEKOLAH DI SD MUHAMMADIYAH KARANGPLOSO - Utami Ariwibowo; Muhamad Fakhrur Saifudin (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
This study aims to describe and find out the factors supporting and inhibiting the implementation of religious character education through school culture in SD Muhammadiyah Karangploso. The background of this research is the implementation of character education that has not been maximally applied in Indonesia. The school emphasizes verbal and numerical abilities while the ability to instill faith and piety is ignored. Muhammadiyah Karangploso Elementary School is an elementary school that seeks to instill religious character. These efforts are in line with the vision of the school that is the realization of Muslim people who have noble, intelligent, skilled, independent, noble culture, useful for society and the country. This type of research is descriptive research 'using a qualitative approach. Research subjects are the principal, teachers, and students. The object of this research is the whole process of activities regarding the implementation of religious character planting through school culture in SD Muhammadiyah Karangploso. The results showed that Muhammadiyah Karangploso Elementary School had implemented religious character planting well, and referred to indicators of success according to the Ministry of National Education and expert opinion but there were still obstacles related to its implementation including environmental conditions of students who were not friendly so that it had an impact on the way students behaved.